The Nazi hunters - Ashman, Charles R.; Wagman, Robert J. (Warner Books, Inc., 1988)
Focuses on the Nazi hunters Simon Wiesenthal, the Klarsfelds, Edgar Bronfman, Elan Steinberg, Israel Singer of the World Jewish Congress, Rabbi Marvin Hier, Neal Sher, and the Justice Department's Office of Special Investigations.